Suburban sketches / by W.D. Howells. - Howells, William Dean, 1837-1920. (Tufts University. Tisch Library., 2016)
New and enlarged edition /with illustrations by Augustus Hoppin.; 1 online resource (255 pages, 10 unnumbered leaves of plates) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.